Asymptomatic primary biliary cirrhosis. Issue 6 (June 1973) - Fox, R. A.; Scheuer, P. J.; Sherlock, Sheila
Abstract : Four asymptomatic patients are described with raised serum alkaline phosphatase values and a positive serum mitochondrial antibody test. In all four needle liver biopsy showed destructive bile duct lesions. Lymphocyte transformation to phytohaemagglutinin was normal in three and impaired in one who also suffered from rheumatoid arthritis. Two patients showed normal skin and serological test responses to dinitrochlorobenzene and haemocyanin. These four patients are believed to be suffering from asymptomatic primary biliary cirrhosis.